Impact of Saroda Dam Construction on Biotic and Abiotic Components of the Sabri and Khol River in Kabirdham, Chhattisgarh, India - Annpoorna Sharma,; Dr. Manoj Singh, (International Journal of Scientific Research in Science and Technology, 2024)
Currently, most of the large rivers worldwide have been fractured due to the construction of hydroelectric dams. The process of damming rivers has a substantial effect, as it not only creates a physical obstruction between areas upstream and downstream, but also poses a considerable danger to the local plant and animal life. In order to comprehend the fundamental alterations in biotic and abiotic factors both upstream and downstream of the dam, we conducted a study on the river near Kabirdham, Chhattisgarh, which has been affected by the Saroda Dam. The construction of the Saroda Dam caused the fragmentation of the river near Kabirdham. This study examined the biotic and abiotic factors of the river in three distinct habitats: S-1 (located upstream of the reservoir site), S-2 (located at the impounded site), and S-3 (located downstream of the dam). The data analysis disclosed substantial disparities across the examined locations. The water temperature, transparency, pH, nitrate, and phosphate increased in the impounded site (S-2), while turbidity, water velocity, DO, free CO2, and alkalinity decreased in the impounded site (S-2) compared to the natural, free-flowing site (S-1) and downstream site (S-3). The richness and density of Chlorophyceae members dramatically increased in the impounded site (S-2) in contrast to the free-flowing site (S-1) and downstream tailwater site (S-3). Great differences in fish assemblages throughout the fragmented habitats were also noted. The impounded site (S-2) had a total of only four fish species documented, while the downstream location (S-3) had sixteen species and the natural free-flowing upstream reservoir site (S-1) had twenty-one species.
Keywords: River Fragmentation; Ichthyo-Faunal Diversity; Phytoplankton; Gene Pool; Physicochemical Parameters